Geological characterization of the three high-priority landing sites for the Luna-Glob mission. (1st November 2018) - Ivanov, M.A.; Abdrakhimov, A.M.; Basilevsky, A.T.; Demidov, N.E.; Guseva, E.N.; Head, J.W.; Hiesinger, H.; Kohanov, A.A.; Krasilnikov, S.S.
Abstract: Twelve landing ellipses (15 × 30 km each) were previously selected during the preliminary science and safety assessment of details of the Russian Luna-Glob mission. In our work, we have conducted a photogeological and topographical study of the top three most desirable landing ellipses (ellipses 1, 4, and 6) and modelled the thickness of the lunar basin ejecta at these locations in order to characterize their safety conditions and possible sources of materials. For all three potential landing sites large (>0.3–0.5 m) boulders do not represent a significant threat to the mission. The major safety concerns are small but abundant craters whose walls are steeper than the technical constraint of 7°. We have collected the data on density, areal fraction, and the mean distance between the neighboring steep-wall craters, which allow us to rank the safety of terrains within each landing ellipse. A set of morphologically and topographically distinctive units make up the surface of the landing ellipses. The units form two groups, the hilly units and the flat plains. The hilly units within the ellipses 1 and 6 are among the safest terrains. The flat plains of ellipses 1 and 4 represent the most unsafe surfaces. The ejecta of the South Pole-Aitken basin (SPA) strongly dominate the Luna-Glob landing zone and constitute ∼95% (by volume) of materials than can be encountered and analyzed within the landing ellipses. For example, the hilly units in the ellipses 1 and 6 likely represent materials of the SPA ejecta. In the ellipse 4, the hilly unit corresponds to the ejecta of Moretus crater and may represent materials excavated from below the SPA ejecta blanket. However, the small area and configuration of the hilly unit in ellipse 1 and abundant small steep-wall craters on the hilly unit in ellipse 4 make them either a difficult or an unsafe target to land. The flat plains in ellipses 1 and 4 are the most unsafe terrains to land because of the abundant steep-wall craters on their surfaces. Materials ejected by the large craters Boguslawsky and Boussingault from the lower portions of the SPA ejecta blanket make up the majority of the hilly unit in the landing ellipse 6. This unit is among the safest terrains in all top three landing ellipses of the Luna-Glob mission. Highlights: The sources of materials in the top-three (1, 4, 6) Luna-Glob landing sites were analyzed. The ejecta of the SPA basin dominate the entire Luna Glob landing area. Flat plains in ellipses 1 and 4 may represent materials ejected from below the SPA ejecta. Flat plains in ellipses 1 and 4 are the most unsafe units to land. Units in ellipse 6 may represent materials from the lower portions of the SPA ejecta.